Role of Social Media in Psychiatry During Pandemic: A Potential Risk for Suicidal Ideation. Issue 9 (September 2021) - Memon, Roha Saeed; Ullah, Irfan; Shoib, Sheikh; Qudrat, Qudrat Ullah; de Filippis, Renato
Abstract : Abstract: The COVID-19 pandemic brought with itself significant mental health challenges owing not only to the morbidity and mortality from the infection but also to mitigation strategies of social distancing and self-isolation. Indeed, in the absence of adequate pharmaceutical aids, quarantine and social distancing measures are taken to limit the spread of the SARS-CoV-2 virus. Thus, living in the world of social media, the average usage of social media could be expected to show a sharp rise as measures of social distancing and quarantine are adopted to contain the pandemic. In this context, social media could be thought of as an additional preventative resource aiding the containment of the pandemic by being a key network for communication during a crisis. Because social media usage cannot be brought down to null considering the fact that it does have some positive aspects to it in terms of disposition of useful information, we could alternatively modify the reporting to be more responsible. In conclusion, we could hypothesize that social media might surge responses for some adverse mental health conditions, increasing fear, anxiety, and panic responses, even spreading suicidal ideation and therefore impacting incidence of suicide in some way. Moreover, social media should be carefully handled, particularly during the pandemic, as social media engagement spiked. Indeed, suicide news, when not reported adequately, and most dangerous social media challenges could have devastating effects among youngest users.